INOVASI PELAYANAN “JEMPUT BOLA TERPADU” DALAM MENINGKATKAN CAKUPAN KEPEMILIKAN DOKUMEN KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDOARJO - Veronica Adekus Suwandy (Jurnal Penelitian Administrasi Publik, 2019)
The development of technology has encouraged the government as a public organization to always innovate services to the community. This is intended to accelerate the improvement of Coverage of Population Document. This study included qualitative descriptive research. The location of this research is the Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo. The results of this research: 1) Relative Advantage Attributes can be said to have succeeded in increasing the scope of ownership of population documents. 2) Conformity Attributes can be said to have succeeded in increasing the scope of ownership of population documents. 3) Complexity attributes can be said to have succeeded in increasing the coverage of ownership of population documents. 4) Possible Tried Attributes can be said to have succeeded in increasing the scope of ownership of population documents. 5) Ease Attributes Observed can be said to have succeeded in increasing the coverage of ownership of population documents. Keywords: Service Innovation, Coverage of Population Document Ownership